The Regulation of Paid Care Workers’ Wages and Conditions in the Non-Profit Sector: A Toronto Case Study - Charlesworth, Sara (Relations industrielles / Industrial Relations, 2010)
This paper aims to contribute to understandings of the broader regulatory context in which remuneration for care work is negotiated and determined. It draws on a case study of the non-profit sector of Toronto and moves beyond an exclusive focus on the formal regulation of the employment relationship to include other crucial regulatory mechanisms in the analysis. The paper attempts to map the intersections between these different forms of regulation and to identify the effects they produce in practice.The paper identifies four main regulatory forces that shape the quantum and basis of the wages and non-wage benefits paid to care workers. Firstly, industrial relations regulation plays an important role not only through the demarcation between unionized and non-unionized agencies, but in demarcations between smaller and larger agencies, between full-time and part-time workers and between regular and elect-to work workers. Secondly, the sources and structure of the social services funding market directly limit care worker remuneration and can work to trump the impact of unionization. Thirdly, the regulatory force of the gendered undervaluing of paid care work is reflected in and intertwined with changes in the protection offered to employees via industrial regulation. Finally, the gendered architecture of paid care work, including size of agency or whether the care work is undertaken in the home or in an institution, contributes to different outcomes for different groups of workers undertaking similar work.The interaction of these regulatory forces plays out in the wage and non-wage outcomes in all social services work at the labour market, industry and workplace levels. While the non-profit sector in Toronto provides one specific context in which this occurs, these regulatory forces, particularly the normative effect of gender, are present in other provincial and national contexts. This is at least partly because the community services funding market in other developed countries is underpinned by the same features of new public management present in Canada.